Album of overtures, vol. 1 - ROBERTS, Chas. J. (Carl Fischer, 1913)
The magic flutenPoet and peasantnQueen of AutumnnCzaar und ZimmermannnHungarian LustspielLa Dame BlanchenYThe Merry Wives of WindsornZampanLight Cavalry